2014
DOI: 10.1007/s10098-014-0812-x
|View full text |Cite
|
Sign up to set email alerts
|

Biodesulfurization: a mini review about the immediate search for the future technology

Abstract: A major concern among the environmental agencies includes the emission of sulfurous gas into the environment. Consequently, the oil agencies are in constant search of alternative processes aiming the reduction of sulfur content in fuels. One of the technologies commonly used is the hydrodesulfurization (HDS), but this is a high-cost process that also requires high temperature and pressure. A complementary alternative to HDS is biodesulfurization (BDS) involving the use of specific microorganisms to the removal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(52 citation statements)
references
References 63 publications
2
50
0
Order By: Relevance
“…It has been shown that bacteria harboring identical dsz genes provide different BDS rates due to the influence of the host metabolism (Kilbane, 2006 (Kilbane, 2006;Li et al, 2008;Ma et al, 2006;Shavandi et al, 2009; Wang et al, 2011). Despite all these successful trials to produce genetically improved biocatalysts, so far, none of the deployed gene manipulation techniques has resulted in a BDS rate meeting the industrial requirement for the development of a commercial BDS process (Boniek et al, 2015;Kilbane, 2006). Moreover, no real efforts have been taken to solve HBPS and 2HBP-related feedback inhibition of the BDS process (Abin-Fuentes et al, 2013).…”
mentioning
confidence: 99%
“…It has been shown that bacteria harboring identical dsz genes provide different BDS rates due to the influence of the host metabolism (Kilbane, 2006 (Kilbane, 2006;Li et al, 2008;Ma et al, 2006;Shavandi et al, 2009; Wang et al, 2011). Despite all these successful trials to produce genetically improved biocatalysts, so far, none of the deployed gene manipulation techniques has resulted in a BDS rate meeting the industrial requirement for the development of a commercial BDS process (Boniek et al, 2015;Kilbane, 2006). Moreover, no real efforts have been taken to solve HBPS and 2HBP-related feedback inhibition of the BDS process (Abin-Fuentes et al, 2013).…”
mentioning
confidence: 99%
“…In this sense, the regulations increasingly require lower levels of sulfur [2,3]. One of the main challenges of modern refineries is to achieve the demanded regulations since the existing process, called hydrodesulfurization, is not capable to remove sulfur to such low levels [1,4].…”
Section: Introductionmentioning
confidence: 99%
“…Rhodococcus erythropolis sp. is one of the most promising biocatalysts [4,6,7] principally due to its capacity to convert dibenzothiophene (DBT) [8,9], a model of the recalcitrant compounds present in oil, into 2-hydroxybiphenyl (2-HBP) and sulfate through the 4S metabolic pathway [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…However, studies to improve the cost-effectiveness of the process are on-going. BDS technology is the future focus of most researchers throughout the world today because it employs microbes as bio-catalysts to remove sulphur from compounds that are recalcitrant to HDS [66]. Although, BDS has showed lower capital cost of desulphurization over the HDS process, however its low rate of conversion coupled with difficulties encountered in monitoring the operating conditions of bacteria growth and desulfurization capabilities hinder its commercial utilization [71].…”
Section: Existing Technologies For Desulphurizationmentioning
confidence: 99%
“…Therefore, new cost effective methods are sought throughout the world. Attention has been shifted to biodesulfurization (BDS) as an alternative method or a complementary process of removing sulphur containing compounds from fuels [65][66][67][68][69][70]. However, studies to improve the cost-effectiveness of the process are on-going.…”
Section: Existing Technologies For Desulphurizationmentioning
confidence: 99%